2021
DOI: 10.1016/j.csbj.2021.04.014
|View full text |Cite
|
Sign up to set email alerts
|

Identification of multipotent drugs for COVID-19 therapeutics with the evaluation of their SARS-CoV2 inhibitory activity

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
29
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 154 publications
(51 reference statements)
3
29
2
Order By: Relevance
“…Johnson et al reported that stable introduction of the spikeactivating protease TMPRSS2 further enhanced susceptibility to infection by 5-to 10-fold. 45 Kumar et al 47 assessed the activity of montelukast using an in vitro cell culture model of SARS-CoV2 in VeroE6 cells, and the IC 50 of montelukast was measured as 18.82 mM, which fits well with our results.…”
Section: Discussionsupporting
confidence: 86%
“…Johnson et al reported that stable introduction of the spikeactivating protease TMPRSS2 further enhanced susceptibility to infection by 5-to 10-fold. 45 Kumar et al 47 assessed the activity of montelukast using an in vitro cell culture model of SARS-CoV2 in VeroE6 cells, and the IC 50 of montelukast was measured as 18.82 mM, which fits well with our results.…”
Section: Discussionsupporting
confidence: 86%
“…Among them two proteases are vital for virus replication which includes chief protease (M PRO ) defined as 3 C-like protease (3CL PRO ) and papain-like protease (PL PRO ) [ 54 , 55 , 56 ]. M PRO and PL PRO process the polypeptide pp1a and pp1ab in a sequence specific manner to generate 16 dissimilar non-structural proteins.…”
Section: Resultsmentioning
confidence: 99%
“…3CL pro plays an essential role in processing polyproteins, the resultant products of which are subsequently utilized in the production of new virions. Additionally, there is a known clinical crossover between ebastine and levocetirizine, the latter considered more potent [27] , [30] , [31] , [32] , [33] , [34] .…”
Section: Introductionmentioning
confidence: 99%